Ration formulation and feed guides - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Ration formulation and feed guides by J Mtimuni 1995 57pp ISBN 99908 9060 9 Dr J Mtimuni, Bunda College of Agriculture, PO Box 219, Lilongwe, MALAWI